INISIATIF MASYARAKAT PESISIR SEMARANG DALAM ADAPTASI PERUBAHAN IKLIM - Arief Khristanto (Jurnal Riptek, 2017)
Semarang City has vulnerability to climate change due to the existence of several phenomena such as increasing temperature, rainfall and sea water level. Coastal area is the most vulnerable areas. Communities in the coastal areas engaged in the fisheries sector are the most affected communities. A number of climate change adaptation efforts have been implemented by the coastal communities of Semarang City with the support of various parties. It is therefore necessary to identify the initiatives of coastal communities in adapting to climate change as well as related matters. The analysis used in this study is descriptive analysis. Data collection is done through field observation and in-depth interviews. Selection of respondents is done by purposive that is key person actively involved in various adaptation efforts of climate change. The result of this study is that a number of initiatives that have been done by coastal communities of Semarang City in climate change adaptation, among others; planting of mangroves, construction of old tire breakwater construction, Ecological Mangrove Restoration (EMR) combined with mangrove transplantation and development of hybrid engineering breakwater construction and tilapia cultivation in brackish water.